2021
DOI: 10.1177/1120672121990561
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of residual ellipsoid zone and its correlation with visual functions in patients with cone-rod dystrophy

Abstract: Cone-rod dystrophy (CORD) is one of the inherited retinal diseases that result in central visual field deterioration and decreased visual acuity (VA). In CORD patients, impaired photoreceptor cells are observed as the disruption of ellipsoid zone (EZ) on optical coherence tomography (OCT) images. In the present study, we calculated the index of residual EZ (rEZ) to quantify the function of photoreceptor cells and investigated the correlation between rEZ index and visual functions. Twenty-six eyes of 13 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Freund and associates recently reported that BCVA was correlated with the degree of EZ integrity in patients with acquired vitelliform lesions [9]. We have reported a novel method for quantifying residual EZ index in macular diseases, such as CSC or cone-rod dystrophy [10,11]. It would be of interest to further investigate the relationships between the EZ integrity and visual function in AOFVD eyes.…”
Section: Discussionmentioning
confidence: 96%
“…Freund and associates recently reported that BCVA was correlated with the degree of EZ integrity in patients with acquired vitelliform lesions [9]. We have reported a novel method for quantifying residual EZ index in macular diseases, such as CSC or cone-rod dystrophy [10,11]. It would be of interest to further investigate the relationships between the EZ integrity and visual function in AOFVD eyes.…”
Section: Discussionmentioning
confidence: 96%
“…Freund and associates recently reported that BCVA was correlated with the degree of EZ integrity in patients with acquired vitelliform lesions 9 . We have reported a novel method for quantifying residual EZ index in macular diseases, such as CSC or cone-rod dystrophy 10 , 11 . It would be of interest to further investigate the relationships between the EZ integrity and visual function in AOFVD eyes.…”
Section: Discussionmentioning
confidence: 99%
“…CORD patients present with decreased visual acuity (VA), impaired retinal sensitivity and color vision loss and sometimes demonstrate peripheral visual field loss at the end stage, followed by rod photoreceptor impairments [ 4 ]. Several studies have revealed a structure-function relationship in eyes with CORD, such as the correlation between VA and residual EZ and between retinal sensitivity and the abnormal autofluorescent area [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%